The Spending behavior of college students under scholarship programs: An assessment of their financial choices and academic progress - Bagaslao, Brylle Jerome T., Huliganga, Erika Eunice B., Manalasysay, Marco Luis N., Nitura, Louisse Anthony A., Relacion, John Patrick D., Tutaan, Jhasmin Eryka F. 4 0 16; 5
ABSTRACT: The study aims to determine the spending behavior of college students in Manila City in terms of Academic Purposes, Food, and Transportation, as they manage the financial aid that they are receiving from scholarship programs. It prioritizes on how college students in Manila utilize their monthly allowance. The researchers would like to analyze if there is any correlation between the demographic profile with their spending behavior. The study is composed of 100 college students in Manila from the university of Pamantasan ng Lungsod ng Maynila. The data gathered were collected through quantitative survey questionnaire. The researchers determined that the financial aid that the college students are receiving has a significant effect on their spending behavior. The study also discovered that it improves the academic performance of the majority of college students in Manila City. The significance of scholarship programs to college students in Manila City was also recognized, as it decreases the stress that they face while continuing to study at their respected schools. The aforementioned scholarship program assists them in completing their degree and, ultimately, assisting their family in improving their quality of life. Keywords: Demographic Profile, Spending Behavior, Academic Purposes, Food, and Transportation
Research Paper: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2